1973
DOI: 10.2172/4480451
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo photon codes: MCG and MCP

Abstract: Codes: MCG and MCP losv/l y alamos scientific laboratory of the University of California LOS ALAMOS, NEW MEXICO 87544 UNITED STATES ATOMIC ENERGY COMMISSION CONTRACT W-7403-ENG. 36 &r THIS oocu&EJjTis DMiiHnra This report was prepared as an account of work sponsored by the United States Government. Neither the United States nor the United States Atomic Energy Commission, nor any of their employees, nor any of thair contractors, subcontractors, or their employees, makes any warranty, express or implied, or assu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1974
1974
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…The photo-atomic data in the ENDF/B-VI format are based on the evaluated photon data library (EPDL97) [42]. However, the work supporting this report observed that the sections of code describing the form factor evaluation of coherent and incoherent scattering had not been updated since their precursor code, MCP, was written in 1973 [43]. This legacy code results in significant inaccuracies in photon spectra computed by MCNPX when simulating geometries that are typical of NRF experiments [44].…”
Section: Appendixmentioning
confidence: 92%
“…The photo-atomic data in the ENDF/B-VI format are based on the evaluated photon data library (EPDL97) [42]. However, the work supporting this report observed that the sections of code describing the form factor evaluation of coherent and incoherent scattering had not been updated since their precursor code, MCP, was written in 1973 [43]. This legacy code results in significant inaccuracies in photon spectra computed by MCNPX when simulating geometries that are typical of NRF experiments [44].…”
Section: Appendixmentioning
confidence: 92%
“…The photo-atomic data in the ENDF/B-VI format are based on the evaluated photon data library (EPDL97) [49]. However, the work supporting this report observed that the sections of code describing the form factor evaluation of coherent and incoherent scattering had not been updated since their precursor code, MCP, was written in 1973 [50]. This legacy code results in significant inaccuracies in photon spectra computed by MCNPX when simulating geometries that are typical of NRF experiments [51].…”
Section: Rayleigh Scattering In Mcnp D1 Introductionmentioning
confidence: 92%
“…The derivation and use of momentum transfer values in MCNP has been poorly documented. MCP and MCNP user manuals describes q in units of cm −1 ; [48,50] however, the data tabulated in MCNPX are in units ofÅ −1 [52]. The legacy problems in elastic scatter come from the fact that MCNP has historically had a fixed array of q-values for which coherent scattering form factors, C(Z, q) are defined.…”
Section: Rayleigh Scattering In Mcnp D1 Introductionmentioning
confidence: 99%
“…For the photoelectric effect, the ensuing primary and secondary fluorescence are both explicitly simulated for Z P 31 using the method by Everett and Cashwell (1973). For the incoherent and coherent scattering interactions, the electron's binding effects are being accounted for using the method by Cashwell et al (1973). Secondary electrons are not simulated, and their energy is assumed to be locally deposited.…”
Section: Physics Modelmentioning
confidence: 99%